PENGARUH TUNJANGAN SERTIFIKASI TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN ALLA KABUPATEN ENREKANG - Latief, Fatmawati; Hakim, Lukman; Burhanuddin, Burhanuddin (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to analyze the teachers who had received certification allowances,  performance of teachers, as well as the influence of the motivation of teachers who had received certification allowances on performance achievement. The method used in this study was a quantitative research method with samples taken from elementary school teachers in Alla District, Enrekang District by stratified random sampling of 80 people. The data analysis technique used  descriptive statistical analysis techniques and simple linear analysis techniques with analyzed by  SPSS version 24. The results of this study showed that there was an influence between the certification allowance on teacher performance which was obtained by a constant of 43 explaining that the consistent value of the certification allowance variable was 43 The regression coefficient X of 0.7 states that for every 1% change in the value of the certification allowance, the value of teacher performance increased by 0.7. The coefficient was positive, so it could be said that the direction of the influence of variables X with Y was positive. The correlation coefficient of 0.5 implied that the influence of the certification allowance variable was strong, so it could be concluded  that the stronger the influence of the certification allowance the teacher performance was be stronger or increasing.